Assessment of the genotoxic potential of a migraine-specific drug by comet and cytokinesis-block micronucleus assays. (3rd May 2020) - Cayir, Akin; Cobanoglu, Hayal; Coskun, Munevver
ABSTRACT: Background : Eletriptan is a migraine-specific drug-containing the triptan group. In terms of drug safety, the present study aimed to investigate the genotoxic potential of eletriptan. Research design & methods : We conducted our study by using the cytokinesis-block micronucleus cytome (CBMN) assay, a comprehensive method for measuring micronucleus formation, and a sensitive method for detecting DNA-strand breaks. In the assay, cytokinesis-block proliferation index and the frequency of micronuclei were evaluated in lymphocytes treated with three different concentrations (1, 10 and 25 µg/ml) of eletriptan for 48 hours. In comet assays, DNA damage was evaluated in leucocytes treated with three different concentrations (1, 10 and 25 µg/ml) of eletriptan for an hour. Results : Eletriptan did not induce cytotoxicity nor any increased micronuclei frequencies. While the comet parameters % DNA in tail, tail moment, and the olive moment was found to be significantly increased at 10 and 25 µg/ml, the cytokinesis-block proliferation index values were not. Conclusion : These findings suggest that eletriptan is non-cytotoxic but potentially weakly genotoxic at higher concentrations (10 and 25 µg/ml).